Cytotoxicity-Associated gene (CagA) Producing Helicobacter pylori Increased Risk of Developing Colorectal Carcinoma in Iraqi Patients. - Wasan Abdulilah Bakir; Noor Hashim Ismail; Ayser Hameed Latif; Dina Wael Abd; Zena Zaki Saied (College of Pharmacy / Mustansiriyah University, 2014)
Infection with Helicobacter pylori, particularly with strains positive for cytotoxicity- associated gene (CagA) gene, increases the risk of gastric adenocarcinoma and it may be associated with carcinogenesis in extra gastric target organ. The aim of this study to explore the possible association between CagA positive H. pylori and colorectal carcinoma and determine the association with clinico-pathological features. Paraffin embedded tumor specimens from (49) patients with colorectal adenocarcinoma and (30) healthy control were assessed by in situ hybridization for the expression of H. pylori CagA mRNA. Statistical analysis of H. pylori CagA positive expression revealed highly significant difference in colorectal carcinoma patients than in control group. There was no relationship between H. pylori CagA positive expression and range of clinicopathological features. Among patients infected with H. pylori CagA positive is associated with increased risk for colonic cancer.